The Influence of Social Support, Stigma, and Coping Strategies on the Quality of Life of Families of Schizophrenia Patients - Lia Novianty (GLOBAL HEALTH SCIENCE GROUP, 2026)
Schizophrenia is a serious mental disorder that affects not only patients, but also the quality of life of their families as primary caregivers. The prevalence of schizophrenia in Indonesia reaches 6.7 per 1,000 households, with West Java being the province with the highest prevalence. Objective to analyze the influence of social support, stigma, and coping strategies on the quality of life of families of schizophrenia patients at the UPTD Puskesmas Sukabumi in Sukabumi City. A correlational study design with a cross-sectional approach was used. The population consisted of families of schizophrenia patients, with a sample of 60 families selected using simple random sampling. Data were collected using validated and reliable questionnaires, with a validity index p-value < 0.05 and reliability > 0.70, namely the SSQ, ISMI, WOC, and S-CGQoL questionnaires. Statistical analysis was performed using the chi-square test and logistic regression. Bivariate analysis showed a significant effect of social support (p = 0.000), stigma (p = 0.000), and coping strategies (p = 0.000) on quality of life. Multivariate analysis showed coping strategies as the most dominant factor (p = 0.002; OR = 38.400). Social support, stigma, and coping strategies influence quality of life, with coping strategies being the most dominant factor affecting quality of life.